Microstructural Analysis of Intermetallic Ni5Al3 Thin Films - Joseph Sahaya Anand, T; Ngan, A.H.W. (Faculty of Mechanical Engineering, UTeM, 2010)
The possible magnetic transition phenomenon obtained is postulated particularly on the Nickel Aluminum (Ni5Al3) thin films of different thickness. It was found that the film resistance exhibits a linear but mild increase over the initial temperature range, followed by a transition to a relatively rapid decline in the resistance after attaining maximum at ~170ºC. This positive temperature coefficient of resistance (TCR) makes this material suitable for magneto resistor applications. The same observations were made on two different sputtering systems with different deposition conditions, indicating that the magnetic transition is a highly reproducible phenomenon.